Clinical characteristics, management, maternal and neonatal outcome among seven severe and critically ill pregnant women with COVID-19 pneumonia - Hazari, Komal Sundeep; Paulose, Litty; Kurien, Nimmi; Mohammad, Hozaifah; Elgergawi, Taghrid Faek A; E Fazari, Atif Bashir; Hassan, Amar (Clinical Journal of Obstetrics and Gynecology, 2020)
Pneumonia caused by the Novel coronavirus disease 2019 (COVID-19) is a highly infectious disease and the ongoing outbreak has been declared as a Pandemic by the World health organization. Pneumonia is a serious disease in pregnancy and requires prompt attention. Viral pneumonia has higher morbidity and mortality compared to bacterial pneumonia in pregnancy. All efforts are well exerted to understand the newly emerged disease features but still some areas are gray. The treatment is primarily supportive with antivirals, steroids, anticoagulation and antibiotics for secondary bacterial infection. Severe cases require intensive care monitoring with oxygen support, mechanical ventilation. Investigational therapies include convalescent plasma, cytokine release inhibitors and other immunomodulatory agents like interferons. The mortality appears driven by the presence of severe Adult Respiratory Syndrome (ARDS) and organs failure. COVID pandemic is a challenging and stressful socio-economic situation with widespread fear of infection, disease and death. In the specialty of obstetrics and gynecology, studies are being conducted to ascertain the manifestation of disease in pregnant women and the fetal outcome. The aim of our case series is to describe the demographics, clinical characteristics, laboratory and radiological findings, feto- maternal outcome of severe and critical COVID pneumonia in pregnant women in Latifa Hospital.